Strength band training - Page, Philip 1967-; Ellenbecker, Todd S. 1962- (Human Kinetics, 2011)
This book explains how to learn maximize strength, speed, and power in the gym, at home, or on the road. The books shows you why strength bands are the ultimate tool for targeting, isolating, and developing every major muscle group